COVID-19 Preventative Measures: Cleaning and Disinfecting Reusable Bags - Natalie Seymour; Mary Yavelak; Candice Christian; Ben Chapman; Michelle Danyluk (EDIS)
Current evidence suggests that novel coronavirus may remain viable for hours or days on a variety of surfaces. Cleaning followed by disinfection is recommended by the CDC as a best practice measure for prevention of COVID-19 and other viral respiratory illnesses in households and community settings. This new flyer, published by the UF/IFAS Food Science and Human Nutrition Department and written by Natalie Seymour, Mary Yavelak, Candice Christian, and Ben Chapman (NC State University Extension), provides information on safe cleaning and disinfection of reusable bags.